Study of organic semiconducting nanoparticles as a photoactive layer for solar cells - Cheong, Yun Rong (2018)
Organic solar cells (OSCs) are rising in popularity, mainly due to their low cost and wide scale applications. However, the production process usually involves the use of carcinogenic and toxic halogenated organic solvents. Also, annealing is required for better efficiency, making it difficult to print solar cells and some substrates are unable to withstand the high temperatures essential for annealing. The purpose of thermal annealing is to impart an alternating domain of donor-acceptor (DA) regions at nearly exciton diffusion lengths for an efficient charge carrier extraction and transport. To do away with the use of thermal annealing, as well as to minimize the use of environmentally malign organic solvents, we investigate alternative ways to engineer the mesoscale morphology of the active layer. As such, an excellent choice is the use of pre-engineered nanoscale phase separated DA region, inadvertently leading to the bulk heterojunctions (BHJs). Presently, the state of Nanoparticle (NP) OSCs have very low efficiencies, highest capping at 4% with high temperature annealing (200oC) (Stefan Gärtner, 2014). Spin coating is most commonly used to coat the NP thin film on the substrate/device. Traditionally, the thin film morphology of the NP active layer has been achieved through multiple spin coating to ensure adequate coverage and film thickness. However, annealing has been an indispensable post processing step to impart an efficient inter-particle contact. Consequently, this project aims to explore centrifuging technique as a possible replacement of the spin coating technique. Unlike the spin coating technique, the centrifuge technique is less commonly used. The references and papers available are scarce, leading to many experimental hurdles in the process. Nevertheless, we managed to form a thin film on a glass substrate with decent morphology.